2023
DOI: 10.3389/fpubh.2023.1141097
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of wastewater-based disease surveillance to improve health equity in California’s Central Valley: sequential shifts in case-to-wastewater and hospitalization-to-wastewater ratios

Abstract: IntroductionOver a third of the communities (39%) in the Central Valley of California, a richly diverse and important agricultural region, are classified as disadvantaged—with inadequate access to healthcare, lower socio-economic status, and higher exposure to air and water pollution. The majority of racial and ethnic minorities are also at higher risk of COVID-19 infection, hospitalization, and death according to the Centers for Disease Control and Prevention. Healthy Central Valley Together established a was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The Data Descriptor describes data from San Jose, Southeast, SAC, and Davis collected through 12/31/22 and Merced and Modesto through 4/27/22 and 12/2/22-12/31/22. In addition, data from Merced and Modesto from 5/4/21 through 09/29/22 were included in a paper by (Kadonsky et al, 2023), and data from San Jose, Southeast, SAC, and Davis after 12/31/22 were included in a paper by Boehm et al (2023c). The other data have not been published previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Data Descriptor describes data from San Jose, Southeast, SAC, and Davis collected through 12/31/22 and Merced and Modesto through 4/27/22 and 12/2/22-12/31/22. In addition, data from Merced and Modesto from 5/4/21 through 09/29/22 were included in a paper by (Kadonsky et al, 2023), and data from San Jose, Southeast, SAC, and Davis after 12/31/22 were included in a paper by Boehm et al (2023c). The other data have not been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…We accounted for these factors by incorporating a fixed effect into the model for discrete time periods associated with three waves of infections that were apparent over this study period (Figure 3). Kadonsky et al (2023) observed that the wastewater-to-hospitalization ratios remained relatively stable during two COVID-19 waves in two geographically adjacent counties in California’s Central Valley between October 2021 and September 2022. This suggests that the wastewater-to-hospitalization ratios may remain constant in some cases, but the intercept may differ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to deduce the main driver for the change in correlation between wastewater SARS-CoV-2 RNA concentrations and incident COVID-19 cases over time, but we suspect that the change is due to several factors including changes in routine COVID-19 surveillance testing requirements, changes in test reporting, and overall decreases in test-seeking behaviors as the pandemic continues. 19,73,74 Wastewater monitoring data are independent of test-seeking behaviors or test reporting patterns so may be a less biased tool for monitoring public health, particularly in periods characterized by low test-seeking and reporting rates.…”
Section: Resultsmentioning
confidence: 99%
“…DWT uses sub-band coding, which is a technique of dividing the signal into frequency bands or sub-bands, and then sampling each sub-band at a lower rate. The DWT 21 achieves this by passing the signal through a series of high-pass and low-pass filters, which please refer to [33]. We used the normalized wastewater concentration of SARS-CoV-2 RNA 56 detected in each wastewater sample for the two laboratories.…”
mentioning
confidence: 99%